B. A. Prakash (ed.). Kerala’s Economic Development: Issues and Problems. New Delhi: Sage Publications, 1999. 392 pages. Hardbound. Indian Rs 495.00. (The Pakistan Development Review, 2000)
The distinctive development experience of Kerala, which has come to be known as the ‘Kerala Model’, has attracted widespread research interest. Successive state governments have pursued a number of objectives that included increase in per capita income at least to the national level, attaining self-reliance in food, terminating the tenancy system, solving unemployment problems, reducing regional inequalities, and protecting the vulnerable sections of society, particularly the Scheduled Castes and Tribes. The improvements continued till the first half of the 1990s, taking Kerala ahead of India by 25 years in demographic transition. Life expectancy and literacy rates are high, while the birth, death, and infant mortality rates are the lowest in all of India.